Study on sperm motility and velocity parameters of freshly collected mithun semen through computer-assisted sperm analyser (CASA) - KHAN, M H; SINHA, PAPIYA; HAZARIKA, S B; PERUMAL, P (The Indian Journal of Animal Sciences, 2017)
The objective of this study was to evaluate the quality of mithun semen by computer assisted sperm analysis (CASA). Ejaculates (50) were analysed by CASA. Semen motility was evaluated for kinetics parameters. The percentage of total motile and progressive motile spermatozoa were determined. Several velocities parameters were also determined viz., average path velocity (VAP, μm/s), track speed (VCL,μm/s), progressive velocity (VSL, μm/s), lateral amplitude (ALH), beat frequency (BCF, Hz), straightness (%), elongation (%), linearity (%), and area (μm sq). The result revealed a strong positive correlation between various CASA parameters (PMOTVAP, PMOT- VSL, VAP-VSL, VAP-ALH, VSL-ALH, STR-LIN).The present study confirmed the usefulness of CASA for a quick and objective analysis of sperm concentration, motility and other velocity parameters.